Penguatan Moderasi Beragama Pada Santri Madrasah Aliyah (MA) di Pondok Pesantren Ash-Shomadiyah Tuban - Syalwa Navya Mawardha; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2026)
This research aims to describe the strengthening of religious moderation among Madrasah Aliyah students at Pondok Pesantren Ash-Shomadiyah Tuban. This study stems from the phenomenon of radicalism and terrorism emerging amidst Indonesia's diversity. Religious moderation is seen as a strategic policy to maintain social harmony, especially within the pesantren environment. The focus of this research is the forms of activities for strengthening religious moderation and the moderate attitudes demonstrated by the students. The research uses an exploratory qualitative approach with participatory observation, semi-structured interviews, and documentation techniques. Analysis was carried out using the Miles and Huberman model with the stages of data collection, reduction, display, and data verification. Data validity was strengthened through source and technique triangulation. The results show that the strengthening of religious moderation is realized through Matsama activities, the learning of Pancasila and Civics, Sociology, Indonesian History, and Islamic Morals. Additionally, Leadership Training activities involving visits to the Military District Command 0811 Tuban, Kembang Putih Museum, Kwan Sing Bio Temple, and Free Pulpit extracurricular activities. Madrasa and pesantren cultural practices such as independence ceremonies, pilgrimage to the tombs of revered figures, thanksgiving rituals (selametan), and sea offerings also serve as a means of internalizing moderate values. The students' attitudes are reflected in their love for the homeland, appreciation for differences, maintaining harmony through dialogue, and respecting pesantren culture and local wisdom. This strengthening is aligned with the four indicators of religious moderation set by the Ministry of Religious Affairs: national commitment, tolerance, anti-violence, and accommodation of local culture. Keywords: Religious Moderation, MA Students, Islamic Boarding School